2018
DOI: 10.1155/2018/7202548
|View full text |Cite
|
Sign up to set email alerts
|

Propolin C Inhibited Migration and Invasion via Suppression of EGFR‐Mediated Epithelial‐to‐Mesenchymal Transition in Human Lung Cancer Cells

Abstract: Controlling lung cancer cell migration and invasion via epithelial-to-mesenchymal transition (EMT) through the regulation of epidermal growth factor receptor (EGFR) signaling pathway has been demonstrated. Searching biological active phytochemicals to repress EGFR-regulated EMT might prevent lung cancer progression. Propolis has been used as folk medicine in many countries and possesses anti-inflammatory, antioxidant, and anticancer activities. In this study, the antimigration and anti-invasion activities of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…However, NA was also found to be a powerful apoptosis inducer and cell‐cycle inhibitor at the G2/M phase, which functions by activating caspase‐3, caspase‐8, and Bid, and inducing cytochrome c release from the mitochondria into the cytoplasm, thereby showing strong cytotoxic effects on human melanoma cells, with an IC 50 value of 8.5 μM (Chen, Wu, & Lin, 2004). Recently, Pai et al (2018) reported that NA at 10 μM did not affect cell proliferation and cell cycles in epidermal growth factor receptor (EGFR)‐mutated HCC827 cells, whereas it dose‐dependently suppressed cell migration and invasion by downregulating the EGFR/phosphatidylinositol 3‐kinase (PI3K)/protein kinase B (Akt) and extracellular signal‐regulated kinase (ERK)‐mediated epithelial‐to‐mesenchymal transition (EMT) signaling pathways. In addition, NA inhibited epidermal growth factor‐induced migration and invasion, as well as mesenchymal‐like marker expression in EGFR wild‐type A549 lung cancer cells.…”
Section: Pharmacological Properties Of Macaranga‐type Pacific Propolimentioning
confidence: 99%
See 4 more Smart Citations
“…However, NA was also found to be a powerful apoptosis inducer and cell‐cycle inhibitor at the G2/M phase, which functions by activating caspase‐3, caspase‐8, and Bid, and inducing cytochrome c release from the mitochondria into the cytoplasm, thereby showing strong cytotoxic effects on human melanoma cells, with an IC 50 value of 8.5 μM (Chen, Wu, & Lin, 2004). Recently, Pai et al (2018) reported that NA at 10 μM did not affect cell proliferation and cell cycles in epidermal growth factor receptor (EGFR)‐mutated HCC827 cells, whereas it dose‐dependently suppressed cell migration and invasion by downregulating the EGFR/phosphatidylinositol 3‐kinase (PI3K)/protein kinase B (Akt) and extracellular signal‐regulated kinase (ERK)‐mediated epithelial‐to‐mesenchymal transition (EMT) signaling pathways. In addition, NA inhibited epidermal growth factor‐induced migration and invasion, as well as mesenchymal‐like marker expression in EGFR wild‐type A549 lung cancer cells.…”
Section: Pharmacological Properties Of Macaranga‐type Pacific Propolimentioning
confidence: 99%
“…In addition, NA inhibited epidermal growth factor‐induced migration and invasion, as well as mesenchymal‐like marker expression in EGFR wild‐type A549 lung cancer cells. It was, therefore, suggested to be an effective EGFR inhibitor and might become an antitumorigenic candidate compound for lung cancer treatment and/or prevention in the future (Pai et al, 2018). Similarly, NC can suppress fibroblast growth factor 18 (FGF18) by lowering the β‐catenin level in the Wnt/β‐catenin pathway, which can also reduce the phosphorylation level of ERK1/2 in the mitogen‐activated protein kinase cascade.…”
Section: Pharmacological Properties Of Macaranga‐type Pacific Propolimentioning
confidence: 99%
See 3 more Smart Citations